Design and Application of a Power Unit to Use Plug-In Electric Vehicles as an Uninterruptible Power Supply - Sen, Gorkem; Boynuegri, Ali Rifat; Uzunoglu, Mehmet; Erdinc, Ozan; Catalao, Joao P. S. (MDPI, 2016)
Grid-enabled vehicles (GEVs) such as plug-in electric vehicles present environmental and energy sustainability advantages compared to conventional vehicles. GEV runs solely on power generated by its own battery group, which supplies power to its electric motor. This battery group can be charged from external electric sources. Nowadays, the interaction of GEV with the power grid is unidirectional by the charging process. However, GEV can be operated bi-directionally by modifying its power unit. In such operating conditions, GEV can operate as an uninterruptible power supply (UPS) and satisfy a portion or the total energy demand of the consumption center independent from utility grid, which is known as vehicle-to-home (V2H). In this paper, a power unit is developed for GEVs in the laboratory to conduct simulation and experimental studies to test the performance of GEVs as a UPS unit in V2H mode at the time of need. The activation and deactivation of the power unit and islanding protection unit are examined when energy is interrupted.
Keywords: vehicle-to-home; plug-in electric vehicles; uninterruptible power supply; plug-in hybrid electric vehicles; distributed generation; grid-enabled vehicles; Energy & Fuels